Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1186/1471-2407-4-45
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide array comparative genomic hybridization analysis reveals distinct amplifications in osteosarcoma

Abstract: Background: Osteosarcoma is a highly malignant bone neoplasm of children and young adults. It is characterized by extremely complex karyotypes and high frequency of chromosomal amplifications. Currently, only the histological response (degree of necrosis) to therapy represent gold standard for predicting the outcome in a patient with non-metastatic osteosarcoma at the time of definitive surgery. Patients with lower degree of necrosis have a higher risk of relapse and poor outcome even after chemotherapy and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
102
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 25 publications
(24 reference statements)
5
102
3
Order By: Relevance
“…Recently, others and we have identified several chromosomal regions that are recurrently amplified in osteosarcoma by chromosomal comparative genomic hybridization (CGH) and array-based CGH (2)(3)(4)(5)(6)(7)(8)10). Of these, amplification of 6p12-p21 and 17p11.2 appeared to be markers of an early genetic change in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, others and we have identified several chromosomal regions that are recurrently amplified in osteosarcoma by chromosomal comparative genomic hybridization (CGH) and array-based CGH (2)(3)(4)(5)(6)(7)(8)10). Of these, amplification of 6p12-p21 and 17p11.2 appeared to be markers of an early genetic change in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) on ordered BAC-Arrays provides a high throughput, high resolution screening method that can be used to quantitatively measure DNA copy number aberrations in solid tumors, and map such alterations directly on the genome This method of genome scanning has been used to search for genomic regions frequently involved in producing solid tumors including breast, colon, brain, esophagus, and kidney [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This represents a paradigm shift in drug development as this drug was approved based on a tumor biomarker rather than the tumor type or organ of origin. In sarcoma research, Man et al have reported the first application of array-based comparative genomic hybrid ization (aCGH) in osteosarcoma, which identified distinct amplifications and deletions that represent potential therapeutic targets [15] . Similarly, using aCGH and expression arrays, Savola et al have identified important copy number aberrations (CNAs) in Ewing sarcoma and correlated the number of CNAs in the tumor to patient's survival [16] .…”
Section: Dna Mutation and Copy Number Analysismentioning
confidence: 99%